Exosomes: A New Pathway for Cancer Drug Resistance - Zhong, Yunbin; Li, Haibo; Li, Peiwen; Chen, Yong; Zhang, Mengyao; Yuan, Zhendong; Zhang, Yufang; Xu, Zhijie; Luo, Geng; Fang, Yuan; Li, Xu (Frontiers in Oncology, 2021)
Exosomes are extracellular vesicles (EVs) that are secreted into body fluids by multiple cell types and are enriched in bioactive molecules, although their exact contents depend on the cells of origin. Studies have shown that exosomes in the tumor microenvironment affect tumor growth, metastasis and drug resistance by mediating intercellular communication and the transport of specific molecules, although their exact mechanisms of action need to be investigated further. In this review, we have summarized current knowledge on the relationship between tumor drug resistance and exosomes, and have discussed the potential applications of exosomes as diagnostic biomarkers and therapeutic targets.